Reduction of outdoor particulate matter concentrations by local removal in semi-enclosed parking garages: A preliminary case study for Eindhoven city center. Issue 159 (December 2016) - Blocken, Bert; Vervoort, Rob; van Hooff, Twan
Abstract: Traffic is one of the main sources of particulate matter (PM) inside urban areas. This paper provides a preliminary assessment of the potential to reduce outdoor PM concentrations by local removal inside semi-enclosed parking garages. The assessment is performed by computational fluid dynamics (CFD) based on the 3D steady RANS equations and an Eulerian advection-diffusion equation. First, an extensive CFD validation study is performed with gas dispersion wind-tunnel measurements. Next, the case study for Eindhoven city center is conducted on a high-resolution grid including 16 semi-enclosed garages. Traffic intensities on the streets and in the garages are converted to PM10 source terms. The garages are ventilated with outdoor air. Simulations are performed with and without removal units in the garages. The case study is not intended to reproduce a particular pollution episode but to provide a preliminary indication of the potential reduction in PM10 for representative meteorological and traffic conditions. The results show that 594 removal units allow reductions in local outdoor PM10 by up to 50% close to the garages while reductions up to 10% are achieved further downstream. It is concluded that local removal in semi-enclosed parking garages can be an effective strategy towards improved outdoor air quality. Graphical abstract: Highlights: Assessment of potential to reduce outdoor PM by removal in semi-enclosed parking garages. Extensive CFD validation study with gas dispersion wind-tunnel measurements. Case study for Eindhoven city center on high-quality high-resolution grid. Model includes buildings, semi-enclosed parking garages, and removal units. 594 removal units allow reductions in local outdoor PM10 by up to 50%.